The Development of Mindful-Based Dance Movement Therapy Intervention for Chronic Pain: A Pilot Study With Chronic Headache Patients - Majore-Dusele, Indra; Karkou, Vicky; Millere, Inga (Frontiers in Psychology, 2021)
Chronic pain is of significant global concern. There is growing evidence that body–mind therapies and psychological approaches can contribute toward changing chronic pain perceptions. This is the first model described in the literature that combines a mindfulness-based approach with dance movement therapy and explores the potential psychological and pain-related changes for this client population. In this paper, the results from the pilot study are presented involving patients with chronic headache recruited in an outpatient rehabilitation setting. Methods: In this pilot study, 29 patients (n = 29) with chronic headache were randomized to either the Mindful-Based Dance Movement Therapy (MBDMT) group or the waiting list control group (treatment as usual, TAU). The MBDMT group was offered 10 sessions in a clinical outpatient rehabilitation setting for 5 weeks. Data were collected pre- and post-intervention and 16 weeks after the intervention was finished. The Hospital Anxiety and Depression Scale (HADS), Patient Health Questionnaire−9 (PHQ-9), Five Facet Mindfulness Questionnaire (FFMQ), and Numeric Rating Scale (NRS) were used as outcome measures. Results: The working model of MBDMT identifies nine therapeutic mechanisms (safe therapeutic environment, mindfulness skills, body awareness, relaxation/releasing, distancing and staying with discomfort, meaning making, self-regulation, acceptance and integration, creative process). Per-protocol analysis reveals statistically significant reduction of pain intensity and depression scores in favor of the MBDMT group, and these improvements were maintained in the follow-up assessment. Conclusions: The results suggest that MBDMT is a feasible and promising therapy approach for chronic pain patients. The pilot study offered sufficient information and preliminary results in the desirable direction to enable the researchers to move to a randomized controlled trial (RCT) stage in order to establish the efficacy of the intervention. Clinical Trial Registration: The study was registered in the www.researchregistry.com, registry (5483).